(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The use of the target cost technique in reducing costs is a technique among the most important modern variables of strategic management accounting that showed the response to the variables of the contemporary business environment, in addition to that the target cost is a method for determining the cost of the product life cycle, which must be sufficient to develop specific job performance and quality, while ensuring its profit desired. Determining the target cost includes subtracting the required profit margin from the competitive market price, and this is what we will present in this research from the profit margin for landing services at the airport. In the Iraqi realities and thus arrive at the cost of the landing service.